Implementasi Akad Salam dalam Transaksi Pre-order (PO) pada Jual Beli Online berbasis Platform E-commerce Perspektif Ekonomi Syariah - Miswinda Miswinda; Sabbar Dahham Sabbar (CV Global Research Publication, 2026)
The development of digital transactions through e-commerce platforms has encouraged the use of pre-order (PO) systems, which conceptually align with the salam contract in Islamic jurisprudence. This study aims to analyze the implementation of the salam contract in pre-order transactions on e-commerce platforms and evaluate its compliance with Islamic economic principles. The research method used is descriptive qualitative with a literature study approach. Data were obtained from scientific journals, research articles, and relevant academic documents, then analyzed inductively using documentation and content analysis techniques. The results show that pre-order practices on e-commerce generally fulfill the basic characteristics of the salam contract, particularly full payment in advance, clear product specifications, and delivery of goods at a later date. However, various problems are still found, such as unclear delivery times, product mismatches with descriptions, limited refund mechanisms, and minimal understanding by business actors and consumers regarding the pillars and conditions of the salam contract. From a sharia economic perspective, the application of the salam contract in pre-order transactions has the potential to support the maqāṣid al-syarī‘ah, especially in safeguarding assets and creating justice, as long as it is supported by adequate regulations, supervision, and utilization of technology.